The Design of the Reader in Educational Settings - Bente Aamotsbakken; Susanne v Knudsen (Stockholm University Press, 2009)
In Norway a new curricular reform was implemented in 2006; a reform characterized by inclusiveness (all school levels up to university level) and a particular focus on five cross-disciplinary basic skills. The skills in question are: reading, writing, numeracy, oral skills and the use of digital media. The reform entails that teachers in all school subjects need an awareness of these skills when teaching their specific curriculum subject. A teacher in mathematics, for example, needs to ensure that the pupils are able to read the mathematical text and write according to the textbook's goals.